2020
DOI: 10.1111/cag.12635
|View full text |Cite
|
Sign up to set email alerts
|

Assessing climate change adaptation progress in Canada's protected areas

Abstract: Climate change represents a new era for protected areas and biodiversity conservation. With the redistribution of species and unparalleled declines in biodiversity, business‐as‐usual practices are unlikely to be effective. Despite progress on many facets of establishing, protecting, and managing protected areas over the past century, some of which may help to lessen or slow the impacts of climate change on biodiversity, more targeted efforts need to be developed and implemented to address growing climate chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…While winegrowers were most adapted to weather events associated with precipitation, the majority of participants had not yet implemented any adaptation strategy specifically to deal with these events. This finding illuminates the limited progress on climate change adaptation by winegrowers in Canada and parallels a similar finding of little progress in Canadian protected areas (Barr et al 2020). More specifically, many operations are vulnerable to frequent and intensive rainfall at key stages of berry development (Jackson and Lombard 1993), which may result in potential losses if climate change exacerbates those events in the future and winegrowers do not implement measures to moderate or avoid harm.…”
Section: Discussionsupporting
confidence: 86%
“…While winegrowers were most adapted to weather events associated with precipitation, the majority of participants had not yet implemented any adaptation strategy specifically to deal with these events. This finding illuminates the limited progress on climate change adaptation by winegrowers in Canada and parallels a similar finding of little progress in Canadian protected areas (Barr et al 2020). More specifically, many operations are vulnerable to frequent and intensive rainfall at key stages of berry development (Jackson and Lombard 1993), which may result in potential losses if climate change exacerbates those events in the future and winegrowers do not implement measures to moderate or avoid harm.…”
Section: Discussionsupporting
confidence: 86%
“…Although implementation of plans to manage protected areas for climate change have historically been rare (e.g. 34 ), a growing body of research provides guidance on climate-smart protected areas planning (e.g. 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concern that Canada is not adequately incorporating climate change adaptation into MPA management is not new (Jessen et al, 2011;Heck et al, 2012). In surveys of protected area practitioners from Canadian federal, provincial, and territorial government agencies and non-governmental organizations (NGOs) conducted in 2006 and repeated in 2018, 83-85% of practitioners stated in both years that their agency had not completed a comprehensive assessment of climate change impacts on the protected area or its management implications (Barr et al, 2020). This, even though over this time frame, most marine and terrestrial practitioners had observed climate change impacts within their protected areas (Whitney and Ban, 2019;Barr et al, 2020).…”
Section: The Canadian Contextmentioning
confidence: 99%
“…The lack of consideration of climate change in recent management plans is not explained by perceived uncertainty about climate change impacts and lack of knowledge about climate change adaptation strategies, but more so by the lack of capacity and financial resources necessary to incorporate climate change adaptation into MPA management (Whitney and Ban, 2019;Barr et al, 2020;Lemieux et al, 2021). Even when protected area practitioners think that adaptation options are affordable and feasible, decision makers and policymakers continue to think that climate change is too unfeasible to address Sharp et al, 2014).…”
Section: Facilitating Climate Change Adaptation In Mpasmentioning
confidence: 99%
See 1 more Smart Citation